Managing fiscal risks of subnational borrowing in Vietnam improving public expenditure quality program. (Metro Manila, Philippines Asian Development Bank, 2017)
This brief summarizes the findings of policy advice prepared by ADB for the Viet Nam Ministry of Finance to support improvements in subnational public borrowing and debt management.
Keywords: Decentralization in government -- Vietnam; Public administration -- Developing countries; Electronic books